Pertumbuhan dan Hasil Tanaman Selada (Lactuca sativa L.) yang Diaplikasi, Teh Kompos,Teh Guano, PGPR, dan Ekstrak Biochar - Eugenia Dos Reis (Fakultas Pertanian, Universitas Timor, 2020)
To determine the effect of a combination of compost tea,guano tea,pgpr,biochar extract on the growth and yield of land lettuce plants This research has been conducted from may July 2019 in the east timor univesity faculty of agriculture experimental field. The research design uses a single randomized complete design ( CDR) 12 treatments 3 replications.The treatment consists of empty land( T0), soil + compost tea(T1), soil + compost tea + guano tea(T2), soil + compost tea + guano tea + PGPR, (T3),soil + compost tea + biochar ekstract (T4), soil + compost tea + biochar ekstract + PGPR (T5), soil + PGPR (T6), soil + compost tea+ PGPR (T7), soil + guano tea (T8) , soil + guano tea + PGPR (T9), soil + biochar ekstract (T10), ), soil + biochar ekstract + PGPR (11). The treatment was repeated 3 times so that there were 36 units of the research pot. Anova variance results showed that the best treatment was found in the combination of tea guano + pgpr which was expressed through the parameters of number of leaves, leaf dry weight, root leght, leaf dry weight, total dry weight and harvest index.